Energy transition in Bangladesh: its implication on employment and skills in the power and energy sector - Alam, Rafat (My University, 2024)
The global energy landscape is undergoing a pivotal transformation, driven by the dual imperatives of sustainable development and climate change mitigation. This transition from traditional fossil fuels to renewable energy sources presents a unique set of challenges and opportunities, particularly in the context of developing nations such as Bangladesh. With its dense population and burgeoning energy needs, Bangladesh stands at a critical juncture in its energy development trajectory. This paper explores the implications of Bangladesh’s energy transition on employment and skill requirements within the power and energy sector. Through a comprehensive analysis, the study aims to project the net employment impact by 2030, taking into account the evolving energy mix and the potential for job creation versus job displacement. The study further delves into the skill shifts necessitated by this transition, identifying key areas where workforce development efforts should be concentrated. Based on the findings, a set of policy recommendations were proposed to optimize employment outcomes in the renewable energy sector, thus facilitating a more inclusive and sustainable energy transition for Bangladesh.
Keywords: Bangladesh; renewable energy sector; renewable energy; sustainable energy